Development of Student Worksheets Based on Argument-Driven Inquiry Learning Model to Improve Students' Critical Thinking Skills - Putri, Rida Aisyah; Admoko, Setyo (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
This study aims to describe the validity, effectiveness and practicality of a student worksheet development using the Argument-Driven Inquiry (ADI) learning model to practice students' critical thinking skills on Hooke's Law material. The type of research in this case is Research and Development with the ADDIE development model. The subjects in this study were 20 students of class XI Mathematics and Natural Sciences 4 at SMAN 18 Surabaya. The data obtained from this study are the results of the validation of the student worksheets, the pre-test and post-test results, and the questionnaire responses to the student worksheets. The research instrument was validated by 2 lecturer The results of the student worksheets based on ADI learning model validation were analyzed using quantitative descriptive analysis This study found that the results of the validation of the average student worksheets of the ADI learning model on Hooke's Law material to practice students' critical thinking skills are 88.6% with valid categories, the average student pre-test and post-test results are 46 and 80.8. The standard gain value is 0.64, which shows the effectiveness of using student worksheets for the argument-driven inquiry learning model in the medium category. The results of the student response questionnaire were 89.16%, with a very practice category. These results show that the development of student worksheets based on ADI learning model obtained valid, effective and practice categories to improve students' critical thinking skills on Hooke's Law material.